Cobalt-nickel based ternary selenides as high-efficiency counter electrode materials for dye-sensitized solar cells. (1st May 2017) - Jiang, Qingsong; Pan, Kai; Lee, Chun-Sing; Hu, Guang; Zhou, Yuhan
Graphical abstract: Co-Ni based ternary selenide counter electrodes show high electrocatalytic activity for the I 3 − reduction, and the dye-sensitized solar cells with Co0.42 Ni0.58 Se counter electrode exhibits the highest photoelectrical conversion efficiency. Highlights: Co-Ni based ternary selenides are synthesized by one-step solvothermal method. Cox Ni1-x Se with different Co and Ni ratios have been applied to DSSCs. Cox Ni1-x Se CEs show high electrocatalytic activity due to the synergistic effect. The PCE of the DSSC with Co0.42 Ni0.58 Se CE is enhanced by 11.2% compared with Pt CE. Abstract: One important challenge in dye-sensitized solar cells (DSSCs) is to design and construct low-cost counter electrodes (CEs) with good electrocatalytic performance. In this work, a one-step solvothermal method was used to prepare cobalt-nickel (Co-Ni) based ternary selenides with different Co and Ni ratios. Co-Ni based ternary selenide films were fabricated by simple spray deposition for applications as low-cost and high-performance CEs in DSSCs. Electrochemical measurements demonstrate that the Co-Ni based ternary selenide CEs exhibit high electrocatalytic activity and strong charge-transfer ability for the reduction of I3 − due to the synergistic effect between Co and Ni ions in Co-Ni based ternary selenides. In particular, Co0.42 Ni0.58 Se CE shows the higher electrocatalytic activity than other Co-Ni based ternary selenide CEs and platinum (Pt) CE. Furthermore, the DSSC with Co0.42 Ni0.58 Se CE exhibits photoelectrical conversion efficiency (PCE) of 6.15%, which is considerably higher than that of the DSSC with Pt CE (5.53%).